TINJAUAN AMALAN PEMBELAJARAN KOPERATIF DALAM KALANGAN PELAJAR TINGKATAN DUA MAKTAB RENDAH SAINS MARA - YAHAYA, AZIZI; YAHAYA, NOORDIN; HASHIM, SHAHRIN; RAMLI, JAMALUDIN; BAHURI, INTAN SAPINAS (Sains Humanika, 2011)
This study was carried out to investigate the influencing factors which affected the cooperative learning styles among form two students in a MRSM. 132 form two students were selected to be the respondents of the study. The reliability and suitability of the questionnaires Cronbach Alpha was used to determine the internal consistency of the questionnaires was at 0.926. The findings indicated that the cumulative mean value for individual factor is 3.88 with 0.52 for the standard deviation. As for peers, the mean value is 4.18 and the standard deviation value is 0.47 followed by teachers factor with 4.17 for the mean value and 0.47 for the standard deviation value. The final factor is the environment with the mean 4.17 and 0.48 for the standard deviation. The findings demonstrate that the peers play the most important role in affecting the cooperative learning style among form two students in MRSM. From the findings, some suggestions are proposed for further research. Amongst the suggestions are to involve other group of respondents for example students in universities or other higher education institution and also students in urban and rural schools.